2021
DOI: 10.3390/ijerph18084182
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Views towards Sars-Cov-2 Mass Asymptomatic Testing, Social Distancing and Self-Isolation in a University Setting during the COVID-19 Pandemic: A Qualitative Study

Abstract: We aimed to explore university students’ perceptions and experiences of SARS-CoV-2 mass asymptomatic testing, social distancing and self-isolation, during the COVID-19 pandemic. This qualitative study comprised of four rapid online focus groups conducted at a higher education institution in England, during high alert (tier 2) national COVID-19 restrictions. Participants were purposively sampled university students (n = 25) representing a range of gender, age, living circumstances (on/off campus), and SARS-CoV-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
116
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(129 citation statements)
references
References 48 publications
8
116
0
5
Order By: Relevance
“…4.1.4. Social Solidarity, Peer-Pressure, and Stigma Social pressure (e.g., relating to the expected reactions of employers, friends, and family to an individual's decision to seek testing or test result) was a sub-focus of 14 studies in this review [23,24,26,27,32,33,38,40,45,46,48,54,67]. Six studies focused on negative pressure from employers and peers [38,40,45,46] or stigma [54,67] as barriers to testing.…”
Section: Logistics Of Testingmentioning
confidence: 99%
“…4.1.4. Social Solidarity, Peer-Pressure, and Stigma Social pressure (e.g., relating to the expected reactions of employers, friends, and family to an individual's decision to seek testing or test result) was a sub-focus of 14 studies in this review [23,24,26,27,32,33,38,40,45,46,48,54,67]. Six studies focused on negative pressure from employers and peers [38,40,45,46] or stigma [54,67] as barriers to testing.…”
Section: Logistics Of Testingmentioning
confidence: 99%
“…A second study of university students demonstrated that mental health status was influential on risk and protective behaviors. Behavioral determinants included thoughts around coping with self-isolation and avoidance of loneliness [2]. In an additional study, protective factors against psychosocial impacts included being non-Hispanic White, being of a higher SES, and being able to spend at least two hours per day outside, demonstrating the influence of differential risk factors across social determinants [1].…”
Section: Discussionmentioning
confidence: 98%
“…With the increasing use of learning platforms such as Zoom, students are "dedicating cognitive resources" impacting their cognitive load leading to "Zoom fatigue" [20]. In prior studies, while some students adapted well to online learning platforms, others struggled, particularly for those without previously established social support [2]. This further endorses our findings and validates the need for administrators to be aware of the issues and challenges students may face, especially during times of change that have been brought about by the COVID-19 pandemic, thus highlighting the need for social and emotional support for students.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations